Micrometric patterning of a borogermanate glass containing terbium by thermal poling to manage luminescence and second order optical properties - Orives, Juliane Resges [UNESP]; Marcondes, Lia Mara; Karam, Lara; Adamietz, Frédéric; Cardinal, Thierry; Dussauze, Marc; Nalin, Marcelo [UNESP] (IOP Publishing, 2024)
Borogermanate glasses containing terbium ions are interesting materials due to their luminescent and magnetic properties. Terbium can present two different oxidation states and the thermal poling technique can be a pertinent way to modulate spatially the oxidation state of these ions. In this work, we demonstrate using a thermo-electrical imprinting process the transfer of micro scaled motifs on the surface of a borogermanate glass containing Tb3+ resulting in a micrometric structuring of the oxidation state of Tb3+/Tb4+ ions. A large change in absorption and luminescence optical properties is observed, arising from the distinct properties of trivalent and tetravalent terbium ions. Correlative micro luminescence, Raman and second harmonic generation measurements were carried out on the patterned poled glass surface. This has demonstrated an accurate concomitant modification of the glass structure accompanying large luminescence changes and the appearance of a second order optical response which could be attributed to a localized space charge implantation. These original results demonstrate how a simple electrical process allows managing multi optical properties but also paves the way to induce static electrical functionalities in a magnetic optical glassy system.
Keywords: control of oxidation; multifunctional glassy material; thermo-electrical imprinting